Comparison of bean cultivars - Barreto, Paulo Diógenes; Bosco, João; Lopes, Edson Batista (Pesquisa Agropecuaria Brasileira, 2014)
The behaviour of 17 bean Phaseolus vulgaris L., cultivars was studied in three different areas of Paraiba, Brazil, during the years of 1916, 1977 and 1978, with respect to production and disease resistance. The results demonstrate that the RC4 cultivar is most stable in terms of production and disease resistance in the different physiographic zones of Paraiba.